Perlakuan mengundi mahasiswa IPTA dalam pilihanraya kampus 2005 kajian di universiti dan kolej universiti awam Malaysia - Ishak, Mohamed Mustafa; Ismail, Syamsul Anuar; Abdul Razak, Muhammad Afifi; Shariffuddin, Mohd Dino Khairri; Omar, Rusdi (Universiti Utara Malaysia, 2007)
Elections constitute an important element in a democratic system. Through elections every qualified citizen would be able to participate directly in this important process of . democracy. In the context of campus politics in institutions of Highest Learning in Malaysia, campus elections constitute one of the important events that occur an each academic year. According to the provisions of the Universities and College Universities Acts (1975), it is the sole responsibility of the university's authority to conduct elections to choose their representatives in the Students Representative Council. Despite the fact that campus elections has long been a recurring event at every public university each year, there has not been many studies conducted to study the pattern of student voting behavior in elections. In fact, a comprehensive study that encompasses the entire public universities with regard to student voting behavior in the campus election has never been undertaken. This study is the first of its kind in Malaysia conducted in the 2005 campus elections in Malaysian Universities. Among others, the focus of the study is to explore the aspect and level of students' knowledge and participation in campus election. The study also attempts to explore factors that influence students in their voting choice. Among other factors examine are ideology, candidate's image, ethnic background and other important issues involved. The findings indicate that there is specific pattern of voting behavior among student of public universities in Malaysia. This study contends that there are two important factors that shape and influence the pattern of voting behavior among students. These factors are the candidate's personal image and internal issues. Furthennore, there are significant differences in terms of factors that influence students' choice between universities and college universities, gender, ethnicity, academic background, school background, and programme of studies.